Dubious deterrence in the East China Sea - Resnick, Evan (2016)
During his recent visit to Tokyo, President Obama declared that the US-Japan alliance covers the contested Senkaku/Diaoyu islands. Unfortunately, the president's deterrent strategy towards Beijing will place the US in a nightmarish predicament should either Japan or China initiate hostilities against the other.